Self-reported mental health in youth with cerebral palsy and associations to recurrent musculoskeletal pain. (January 2015) - Ramstad, Kjersti; Loge, Jon Håvard; Jahnsen, Reidun; Diseth, Trond H.
Abstract Purpose: To explore self-reports on emotional, conduct, hyperactivity and peer problems and on prosocial behaviour in youth with cerebral palsy (CP), compare the reports to normative data and to mothers' reports and to analyse if recurrent CP-related musculoskeletal pain (RMP) influence the self-reports. Methods: Eighty-one youth with CP (mean age 14.2 years, 40 boys) were assessed by clinical examination, interview and the questionnaire Strengths and Difficulties Questionnaire (SDQ) filled in by the youths and their mothers. Gross motor function (GMFCS) was: level I 43%, level II 41%, level III 12% and level IV–V 4%. Results: Compared to normative data, youth with CP reported similar levels of peer problems, less conduct problems (p < 0.01), less hyperactivity problems (p < 0.01) and more prosocial behaviour (p < 0.01). Compared to the mothers' reports, youth with CP reported lower levels of peer problems (p < 0.01). Twenty-six boys (65%) and 28 girls (68%) had RMP. Girls, but not boys with RMP reported a higher level of peer problems (p = 0.02) than youth without RMP. Conclusion: Self-report on mental health in addition to parental proxy-report is important because it yields additional information. Peer acceptance and the impact of pain on peer problems and participation are candidate topics for further research. Implications for Rehabilitation In children and adolescents with CP, self-report on mental health and peer problems is warranted because they provide different information than proxy-report. Self-reported behaviour may be a starting point for counselling and interventions to improve peer acceptance in children and adolescents with CP. When exploring how pain related to CP influences the daily activities of the individual child or adolescent; health care providers should pay special attention to peer problems and female gender.